Increasing Economic Value Creativity With The Making Of MaskAccessories By Students In Organizations: Peningkatan Kreativitas Yang Bernilai Ekonomis Dengan Pembuatan Aksesoris Masker Oleh Anak Didik Di Panti Asuhan - Teti Chandrayanti; Sunreni; Nova Begawati; Rina Asmeri (KPN Kopertis X, 2022)
The use of masks during the pandemic Covid-19 usually is applied by the community, especially in public areas. Various types of masks are sold in the market, both in terms of materials and models. Earloop masks are masks that are commonly worn by men and women because the masker directly was attached to the ear. For Muslim women who wear hijab, wearing earloop masks does not provide freedom, because sometimes the mask must be removed, such as when they are eating, or drinking while they have to wear the veil. Muslim women need masks without disturbing their appearance as Muslim women, therefore it is needed mask accessories such as connectors for earloop masks to be used. The training on making mask accessories/connectors was carried out for students at the Panti Asuhan Aisyiyah. They are girls and wearing veils, totaling 17 people. The service stage was divided into 3 stages: the preparation stage, the implementation stage, and the closing stage. At the implementation stage, all students were given training starting from preparing all the materials used, until they could make mask connectors successfully by themselves. At closing time, all participants presented their mask connectors made for evaluation.Based on this training, they can improve their skills, use connectors for themselves, and sell mask accessories to increase their income. Further, it is expected that they will have the knowledge about other mask accessories that will be needed and will be used by the community, so they can produce maks accessories according to the the demand of the market.